2005
DOI: 10.1111/j.1365-2257.2005.00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype/genotype relationships in sickle cell disease: a pilot twin study

Abstract: The roles of genetic and non-genetic factors in the haematology, growth and clinical features of sickle cell disease have been studied in nine identical twin pairs (six homozygous sickle cell disease, three sickle cell-haemoglobin C disease). A comparison group of 350 age-gender matched sibling pairs, selected to have an age difference of <5 years, was used for assessing the concordance of numerical data. Attained height, weight at attained height, fetal haemoglobin, total haemoglobin, mean cell volume, mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
1
21
0
2
Order By: Relevance
“…Apart from these effects of HbF and of alpha thalassemia, little is known of other genetic factors which might render patients prone to these splenic complications. Furthermore, a search for environmental factors was not supported by a seasonal pattern or clustering of events except for coincidence of attacks of ASS in identical twin studies [17]. The current study, although limited by sample size, used a powerful new technology to examine possible roles of cytokines, chemokines and/or growth factors in patients with a history of ASS or hypersplenism and matched controls available from the Jamaican Cohort Study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these effects of HbF and of alpha thalassemia, little is known of other genetic factors which might render patients prone to these splenic complications. Furthermore, a search for environmental factors was not supported by a seasonal pattern or clustering of events except for coincidence of attacks of ASS in identical twin studies [17]. The current study, although limited by sample size, used a powerful new technology to examine possible roles of cytokines, chemokines and/or growth factors in patients with a history of ASS or hypersplenism and matched controls available from the Jamaican Cohort Study.…”
Section: Discussionmentioning
confidence: 99%
“…Acute splenic sequestration may be more common in subjects with low fetal hemoglobin (HbF) levels [15] and possibly less common with alpha thalassemia [4] which inhibits sickling and although seasonal pattern or clustering of events has not been shown, concurrence of ASS attacks in identical twins [17] may support an environmental risk factor. Hypersplenism appears more common with high levels of HbF and alpha thalassemia, both inhibiting sickling and allowing splenomegaly to persist, and is commonly reported in SS patients in Eastern Province of Saudi Arabia [11] and central India [8], populations associated with these hematologic factors.…”
Section: Introductionmentioning
confidence: 99%
“…25 A pilot study, looking at nine identical twin pairs, tried to disentangle the roles of genetic and nongenetic factors, with interesting but limited results because of the small sample. 26 The following sections summarize current knowledge of the role of genetic and nongenetic modifiers (Fig. 3).…”
Section: Pathoph Ysiol Ogymentioning
confidence: 99%
“…Identical or monozygotic twins occur in 0.3% -0.4% of births, but to be useful for studies of hematology and clinical features, both twins must survive long enough to provide adequate data. These conditions are not frequently met and the largest available series contained six pairs of identical twins in Jamaica (Weatherall et al 2005). A comparison of twin pairs showed that genetic factors influenced growth and hematological indices but that clinical events in the twin pairs were frequently discordant, suggesting the importance of nongenetic influences.…”
Section: Genetic Versus Environmental Factors Modifying Ss Diseasementioning
confidence: 99%